Management information systems for business logistics. Guidelines for SME companies - Królikowski, Jan (Oprogramowanie wspomagające zarządzanie w branży LST. Praktyka przedsiębiorstw sektora MŚP, 2011)
The paper presents the results of research on information system advancement of business logistics companies. The study was carried out among dozens of companies in Łódź region dominated by SME companies. In relation to IS advancement companies are classified into two groups. Group one: companies with intensive use of information systems support and wide range of services in their offer. Group two: companies occasionally using information system and narrower offer. Moreover, the market of information system for business logistics companies is presented and analyzed from the perspective of SME companies. Conclusion towards meeting customer needs is presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 191-202
Keywords: business logistics; information systems; small and medium-sized enterprises